The Challenge of Prenatal Diagnostic Work-Up of Maternally Inherited X-Linked Opitz G/BBB: Case Report and Literature Review - Marialuigia Spinelli; Carmine Sica; Bruno Dallapiccola; Antonio Novelli; Letizia Di Meglio; Pasquale Martinelli (Hindawi Limited, 2015)
Background. Prenatal diagnosis of Optiz G/BBB syndrome (OS) is challenging because the characteristic clinical features, such as facial and genitourinary anomalies, may be subtle at sonography and rather unspecific. Furthermore, molecular testing of the disease gene is not routinely performed, unless a specific diagnosis is suggested. Method. Both familial and ultrasound data were used to achieve the diagnosis of X-linked OS (XLOS), which was confirmed by molecular testing of MID1 gene (Xp22.3) at birth. Results. Sequencing of MID1 gene disclosed the nucleotide change c.1285 +1 G>T, previously associated with XLOS. Conclusions. This case illustrates current challenges of the prenatal diagnostic work-up of XLOS and exemplifies how clinical investigation, including family history, and accurate US foetal investigations can lead to the correct diagnosis.